Developing Fintech-Micro BMT (FMB) Model - Abdullah Haidar (SMART Insight, 2021)
This paper aims to design a financial technology innovation model for Islamic microfinance institutions Baitul Maal wa Tamwil (BMT), namely Fintech Micro BMT (FMB) at the APEX/association scale. Fintech micro BMT is an effort to realize the two main goals of BMT, namely to become an efficient and independent institution (financial self-sufficiency) as a commercial function and to contribute to poverty alleviation as a social function. The research was conducted using qualitative methods through descriptive analysis techniques. The data used are primary data from interviews and secondary data from literature studies. The analysis of the innovation model is carried out using the Business Model Canvas framework, described in the basic prototype of the application and the features of the business scheme, then equipped with an explanation of the simple financial reporting accounting system of BMT and MSMEs, as well as a credit scoring model. The result of this research is a Fintech micro BMT model that maximizes the duality of BMT's commercial (expanding market share) and social (ZISWAF) functions, overcoming the problem of liquidity gaps (mismatch). Both functions are supported by business management and accounting reporting as well as a professional credit scoring model. Fintech micro BMT also realizes BMT's triple bottom line mission, namely economic development, community empowerment, and da'wah to be sustainable. The use of Fintech micro BMT is expected to help BMTs increase their role in expanding the sharia microfinance network, encourage collaboration between BMTs in Indonesia, increase the volume of BMT financial transactions and integrate MSME actors as recipients of ZISWAF financing and donors with BMTs, encourage more transparent markets and reduce risk of information asymmetry in the process of providing financing.